Pollution status, spatial distribution and ecological risk of heavy metals in sediments of a drinking water lake in South Eastern China. Issue 1 (1st January 2021) - Uddin, Mohammad Mazbah; Peng, Guogan; Wang, Ya; Huang, Jaiju; Huang, Lingfeng
ABSTRACT: This study investigates the pollution status, spatial distribution of heavy metals including Cr, Mn, Ni, Cu, Zn, As, Cd and Pb, in sediments from the Longhu Lake, and evaluates possible ecological risk of these metals. Average concentrations of Cu, Zn, Cd and Pb were 2.1, 3.5, 8.0 and 2.5 times higher than Grade I Chinese soil quality standard respectively. The geo-accumulation index indicates that the lake sediments are moderate to heavily contaminated by Zn, Cd and Pb, which may have higher toxic effects than other metals. The potential ecological risk factor ( E i r ) suggests low risk to aquatic organisms except for Cd which has a considerable risk to aquatic biota. Spearman correlation and principal component analysis suggest that Mn, Zn, Cd and Pb possibly having similar anthropogenic sources and behaviors in the lake. Overall, this study suggests that anthropogenic inputs are from local point and non-point sources, runoff and atmospheric deposition.